Предмет: Алгебра,
автор: zzz143
24 решите пожалуйста
Приложения:
![](https://files.topotvet.com/i/26a/26afb1915bdcd430b8fb23767bf3abc2.jpg)
Ответы
Автор ответа:
0
81¹⁵8²⁰ - (6³⁰+1)(6³⁰-1)=(3⁴)¹⁵(2³)²⁰-(6⁶⁰-1)=3⁶⁰2⁶⁰ - 2⁶⁰3⁶⁰+1=1
5²⁴ - (5³-2)(5³+2)(5⁶+4)(5¹²+16) = 5²⁴ - (5⁶-4)(5⁶+4)(5¹²+16) = 5²⁴ - (5¹²-16)(5¹²+16)= 5²⁴ - (5²⁴ - 256) = 256
a²-b²=(a-b)(a+b)
(a^m)^n=a^(mn)
a^mb^m=(ab)^m
5²⁴ - (5³-2)(5³+2)(5⁶+4)(5¹²+16) = 5²⁴ - (5⁶-4)(5⁶+4)(5¹²+16) = 5²⁴ - (5¹²-16)(5¹²+16)= 5²⁴ - (5²⁴ - 256) = 256
a²-b²=(a-b)(a+b)
(a^m)^n=a^(mn)
a^mb^m=(ab)^m
Похожие вопросы
Предмет: Русский язык,
автор: Baha0707
Предмет: Қазақ тiлi,
автор: ernarkoshkarov10
Предмет: Физика,
автор: EnotikPoloska
Предмет: Математика,
автор: tanuschka1002
Предмет: Математика,
автор: Khuhana1989